Water, Sanitation and Hygiene in a Conflict Area: A Cross-Sectional Study in South Kordofan, Sudan - Rofida Asmally; Abdelmalik A. Imam; Abdullatif Eissa; Abubakr Saeed; Ahmed Mohamed; Eahaa Abdalla; Mariam Alazraa M. Esmaeel; Mariam Elbashir; Mohamed H. Elbadawi; Mohammed Omer; Raghad Eltayeb; Ranya Mohammed; et al. (Journal of Epidemiology and Global Health)
Abstract Background The UN General Assembly recognised the human right to water and sanitation through the sixth SDG in 2010. South Kordofan, a state in southern Sudan, faces WASH challenges due to conflict, geographical factors, and inadequate services, impacting over 600,000 residents. Such conflicts are well known for spreading diseases and disrupting WASH-related practices among displaced individuals. Objectives The study aimed to evaluate the quality and availability of drinking water, as well as sanitation and hygiene practices in rural South Kordofan. It also sought to identify factors affecting community satisfaction with WASH services and to establish a data-driven basis for future interventions addressing these issues. Methods A cross-sectional study accompanied a medical mission to South Kordofan, selecting 33 villages from South Kordofan based on healthcare, population, and accessibility. Water samples, patient forms and questionnaires were collected using convenient sampling for targeted villages and for attendants of mobile clinics. Laboratory analyses were conducted on water samples. Descriptive statistics, univariate analysis and logistic regression were used to analyse the data. The used level of significance was 0.05. Results Out of 784 participants, 60.2% were female. Tube wells/boreholes were the primary water source (68.1%), and most participants (70.9%) lived near their water source (less than 30 min). Dissatisfaction with water services was reported by 56.8%, and satisfaction associated with method of delivery (OR = 0.081, CI = 0.024–0.276)), appearance (OR = 0.299, CI = 0.182–0.489), distance (OR = 0.264, CI = 0.099–0.705), water unavailability (OR = 0.477, CI = 0.297–0.765), and obligation to pay (OR = 0.351, CI = 0.185–0.665). Samples showed high levels of contamination, both microbial and physicochemical. Regarding sanitation, over a third of the participants (41.5%) disposed of children’s stool by leaving it outdoors. About 10% of the participants reported having diarrhea during the week before the study. However, about two-thirds of the participants (68.1%) showed good hygienic practices by using soap or detergents for hand washing. Conclusion The study revealed inadequate WASH services, high microbial contamination, and poor water treatment practices. Paradoxically, many participants expressed satisfaction with water services. Sanitation issues and open defecation persist, emphasizing the need for comprehensive interventions. All these negative consequences can be attributed to the armed conflict which resulted in poor awareness about the safety of drinking water, what safe water looks like and proper hygiene practices. Moreover, these conflicts led to disruption of the economical status leading to the absence of proper water purification infrastructure.